Vestibular Rehabilitation After Traumatic Brain Injury: Case Series. Issue 6 (1st June 2016) - Kleffelgaard, Ingerid; Soberg, Helene Lundgaard; Bruusgaard, Kari A.; Tamber, Anne L.; Langhammer, Birgitta
Abstract : Background and Purpose: There has been an increasing focus on vestibular rehabilitation (VR) after traumatic brain injury (TBI) in recent years. However, detailed descriptions of the content of and patient responses to VR after TBI are limited. The purposes of this case series are (1) to describe a modified, group-based VR intervention and (2) to examine changes in self-reported and performance-based outcome measures. Case Description: Two women and 2 men (aged 24–45 years) with mild TBI, dizziness, and balance problems participated in an 8-week intervention consisting of group sessions with guidance, individually modified VR exercises, a home exercise program, and an exercise diary. Self-reported and performance-based outcome measures were applied to assess the impact of dizziness and balance problems on functions related to activity and participation. Outcomes: The intervention caused no adverse effects. Three of the 4 patients reported reduced self-perceived disability because of dizziness, diminished frequency and severity of dizziness, improved health-related quality of life, reduced psychological distress, and improved performance-based balance. The change scores exceeded the minimal detectable change, indicating a clinically significant change or improvement in the direction of age-related norms. The fourth patient did not change or improve in most outcome measures. Discussion: A modified, group-based VR intervention was safe and appeared to be viable and beneficial when addressing dizziness and balance problems after TBI. However, concurrent physical and psychological symptoms, other neurological deficits, and musculoskeletal problems might influence the course of central nervous system compensation and recovery. The present case series may be useful for tailoring VR interventions to patients with TBI. Future randomized controlled trials are warranted to evaluate the short- and long-term effects of VR after TBI.